Characterization and analysis of a collection of Avena sativa L. from Uruguay - Vilaro, M.=700 1 Rebuffo, M.; Miranda, C.; Pritsch, C.; Abadie, T.
(En, Fr, Es)
ilus., 35 ref.
Keywords: AVENA SATIVA; VARIACION GENETICA; CONSERVACION DEL GERMOPLASMA; ITALIA